'HOPE FOR THE EARTH': BIBLICAL PERSPECTIVES AND TRAJECTORIES - Conradie, Ernst M. 1962- (1998)
The notion of 'hope for the earth' calls for some clarification. The context within which it is used here is that of a larger research project, with the same title, registered at the University of the Western Cape. the aim of this research project is to investigate the viability of an eschatological approach to an ecological theology, spirituality and praxix within the South African context.
Keywords: hope on earth